THE BASIC THEORY OF MODERN CHINESE CRIMINAL JUSTICE IN INTERNATIONAL LAW: CHALLENGES AND RECONSTRUCTION IN THE PROCESS OF MODERNIZATION - YU CUI LAN, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Annotatsiya: China's modern criminal justice system is rooted in the integration of traditional legal culture and modern spirit of the rule of law, and its basic theoretical construction needs to respond to value conflicts and institutional tensions in social transformation.By analyzing the historical path, core contradictions and theoretical framework of criminal justice modernization, this paper discusses the balance mechanism between human rights protection and social protection, and provides theoretical support for judicial practice.